Transportation infrastructure and good health in urban China - Tao Bu; Daisheng Tang (Humanities & Social Sciences Communications)
Abstract The process of rapid urbanization has brought forth severe health problems for the urban populations. Examining the health effect from the perspective of transportation systems, rather than solely focusing on the accessibility and utilization of healthcare services, is beneficial in enhancing the well-being of urban populations in China. By incorporating elements such as transportation and health investment, labor productivity, economic growth, and time efficiency into the endogenous growth framework, this article establishes a multiple equilibrium model between transportation infrastructure and laborers’ health capital, which explains how transportation infrastructure affects individual health status through income levels, healthcare services, health literacy, and time allocation. Furthermore, using ordinary least-squares regression under the data of China Health and Nutrition Survey and the China City Statistical Yearbook from 2000 to 2015, the empirical study revealed that laborers living in places with limited medical resources and county-level city experienced a greater improvement in their health status when these places got significant road improvement between cities but not within the city. The mechanism is that intercity roads can help foster economic growth and provide more provision of healthcare services, as well as boost individual incomes and health investment. It can also improve health literacy and time allocation efficiency. The net effect of health outcomes from transportation infrastructure depends on all the influencing factors. Therefore, appropriate policy should encourage multi-level medical cooperation across cities and hospitals to facilitate patients to access to optimal healthcare.